In the framework of regional development, only few of villages which developed by transmigration program expands as Indonesian government expected. Some problems are remote location with poor access, unfertile soil, and lack of supported socioeconomic infrastructure to develop farm enterprises. This research aims to analyze a growth of countryside level, agriculture activity, a society participation and aspiration, and to compile an area development instruction. The result shows that Bukit Mak - Nurharyadi .; Endriatmo Sutarto; Santun R.P. Sitorus (Forum Pasca Sarjana, 2007)
In the framework of regional development, only few of villages which developed by transmigration program expands as Indonesian government expected.  Some problems are remote location with poor access, unfertile soil, and lack of supported socioeconomic infrastructure to develop farm enterprises.  This research aims to analyze a growth of countryside level, agriculture activity, a society participation and aspiration, and to compile an area development instruction. The result shows that Bukit Makmur countryside has the highest hierarchy.  As far as village area from the service center, it has a lower growth of countryside level. Most of people in the village hope to participate in development of their region, especially in developing of prime commodity such as oil palm which is plant in second arable land  through a partnership with some investors which is facilitated by the government.  East Kutai local government policy in developing area stated that Kaliorang transmigration area as a part of development area of Sangsaka Agropolitan.  Infrastructure especially in transportation is a main problem, because of in developing area as an agribusiness district needs a supporting infrastructure upgrading and development and transportation facilities.   Key words: Kaliorang transmigration area, prime commodity, infrastructure development